Construction of the Experience of Mother-Child Bonding in Early Childhood with Speech Delays Due to Gadget Exposure - Gita Fitria Maharani; Roro Setyawati; Mohd Nazri Abdul Rahman; Mahdi Anbari; Endah Silawati (SOSIOEDUKASI, 2026)
This study aims to explore how mothers construct attachment experiences with young children who experience speech delays due to early exposure to gadgets. A qualitative approach using Interpretative Phenomenological Analysis (IPA) was employed with nine participating mothers whose children had been exposed to gadgets since around 1.5 years of age and were undergoing speech therapy. Data were collected through semi-structured interviews, non-participant observation, and analysed idiographically and interpretatively. The results showed that excessive gadget use without supervision weakened key attachment functions, including secure base, proximity maintenance, safe haven, and response to separation stress. Mothers interpreted their children's speech delays as a crisis of maternal identity marked by guilt and role conflict, particularly among working mothers. Gadgets, which were originally interpreted as a practical solution, were reconstructed as a symbol of emotional absence. However, mothers showed reflective capacity to restore attachment through gadget restrictions, increased emotional presence, physical closeness, direct interaction, as well as spiritual coping and family support. This study confirms that speech delay due to gadget exposure is a relational phenomenon closely related to the quality of attachment and the mother's psychological presence in digital parenting.